Maternal Age at Delivery Is Associated with an Epigenetic Signature in Both Newborns and Adults. - Christina A Markunas; Allen J Wilcox; Zongli Xu; Bonnie R Joubert; Sophia Harlid; Vijayalakshmi Panduri; Siri E Håberg; Wenche Nystad; Stephanie J London; Dale P Sandler; Rolv T Lie; Paul A Wade; et al. (PLoS ONE)
Offspring of older mothers are at increased risk of adverse birth outcomes, childhood cancers, type 1 diabetes, and neurodevelopmental disorders. The underlying biologic mechanisms for most of these associations remain obscure. One possibility is that maternal aging may produce lasting changes in the epigenetic features of a child's DNA. To test this, we explored the association of mothers' age at pregnancy with methylation in her offspring, using blood samples from 890 Norwegian newborns and measuring DNA methylation at more than 450,000 CpG sites across the genome. We examined replication of a maternal-age finding in an independent group of 1062 Norwegian newborns, and then in 200 US middle-aged women. Older maternal age was significantly associated with reduced methylation at four adjacent CpGs near the 2nd exon of KLHL35 in newborns (p-values ranging from 3x10-6 to 8x10-7). These associations were replicated in the independent set of newborns, and replicated again in women 40 to 60 years after their birth. This study provides the first example of parental age permanently affecting the epigenetic profile of offspring. While the specific functions of the affected gene are unknown, this finding opens the possibility that a mother's age at pregnancy could affect her child's health through epigenetic mechanisms.